Cues for Directional Hearing in the Fly Ormia ochracea - Mason, Andrew C. (Frontiers in Ecology and Evolution, 2021)
Insects are often small relative to the wavelengths of sounds they need to localize, which presents a fundamental biophysical problem. Understanding novel solutions to this limitation can provide insights for biomimetic technologies. Such an approach has been successful using the fly Ormia ochracea (Diptera: Tachinidae) as a model. O. ochracea is a parasitoid species whose larvae develop as internal parasites within crickets (Gryllidae). In nature, female flies find singing male crickets by phonotaxis, despite severe constraints on directional hearing due to their small size. A physical coupling between the two tympanal membranes allows the flies to obtain information about sound source direction with high accuracy because it generates interaural time-differences (ITD) and interaural level differences (ILD) in tympanal vibrations that are exaggerated relative to the small arrival-time difference at the two ears, that is the only cue available in the sound stimulus. In this study, we demonstrate that pure time-differences in the neural responses to sound stimuli are sufficient for auditory directionality in O. ochracea.